2019
DOI: 10.1016/j.jaci.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Patients with common variable immunodeficiency with autoimmune cytopenias exhibit hyperplastic yet inefficient germinal center responses

Abstract: Patients with CVID+AIC do not contain mucosal microbiota and exhibit hyperplastic yet inefficient GC responses that favor the production of untolerized IgG B-cell clones that recognize both commensal bacteria and hematopoietic I/i self-antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 24 publications
7
78
1
2
Order By: Relevance
“…In another study, Romberg et al showed that germinal centers in lymph nodes from CVID patients with prominent autoimmunity display irregularly shaped hyperplastic germinal centers while germinal centers were scarce and smaller in patients without this history. Hyperplasia in these cases was accompanied by increase in the numbers of circulating follicular helper T cells, decreased regulatory T‐cells and T‐reg function . This germinal center drive appeared to correlate with fewer isotype‐switched memory B cells, lower frequencies of somatic hypermutation, and curiously, increased serum endotoxin in these subjects.…”
Section: Clinical Spectrummentioning
confidence: 92%
“…In another study, Romberg et al showed that germinal centers in lymph nodes from CVID patients with prominent autoimmunity display irregularly shaped hyperplastic germinal centers while germinal centers were scarce and smaller in patients without this history. Hyperplasia in these cases was accompanied by increase in the numbers of circulating follicular helper T cells, decreased regulatory T‐cells and T‐reg function . This germinal center drive appeared to correlate with fewer isotype‐switched memory B cells, lower frequencies of somatic hypermutation, and curiously, increased serum endotoxin in these subjects.…”
Section: Clinical Spectrummentioning
confidence: 92%
“…Lymphocyte immunophenotyping and in vitro proliferation of T cells in response to mitogens is typically normal in CVID . One of the hallmarks of CVID‐like primary immune regulatory disorders with associated AIC is an increase in circulating T follicular helper cells (depicted in Figure ) …”
Section: Primary Immune Regulatory Disorders Spectrum: Alps‐like/ipexmentioning
confidence: 99%
“…Histologic examination of patients with CVID‐like disease with AIC often shows expanded but bizarre arrangement of germinal centers (depicted in Figure ) . Granulomatous inflammation involving the lung, lymph nodes, liver, and skin may also be present .…”
Section: Primary Immune Regulatory Disorders Spectrum: Alps‐like/ipexmentioning
confidence: 99%
See 2 more Smart Citations